Effects of Siwu decoction on chondrocyte proliferation of growth plate in adolescent rats. (23rd May 2019) - Lee, Donghun; Lee, Sun Haeng; Lee, Minwoo; Lee, Sung Hyun; Shin, Yu Jeong; Lee, Jin Yong; Kim, Hocheol; Kim, Young-Sik; Song, Jungbin
Abstract: Ethnopharmacological relevance: According to traditional Korean medicine theory in which children's growth retardation is attributed to blood deficiency, Siwu decoction (SWD), a representative treatment for blood deficiency, was chosen as a sample. Aim of the study : To evaluate the effects of SWD on chondrocyte proliferation of growth plate in adolescent female rats. Materials and methods: Female adolescent rats were allocated to one of the following four groups; SWD 100 and 300 mg/kg, recombinant human growth hormone, and vehicle for 4 days. Tetracycline was intraperitoneally injected at 48 h before sacrifice to obtain a band exhibiting fluorescence by binding newly formed bone. Bromodeoxyuridine was injected at day 2–4 to mark proliferating chondrocytes. To evaluate possible mechanisms of SWD, expressions of insulin-like growth factor-1 (IGF-1) and bone morphogenetic protein-2 (BMP-2) in the growth plate were examined by immunohistochemistry. Results: Treatment with SWD significantly increased the number of BrdU-positive chondrocytes and the new bone formation in the proximal growth plate of tibia compared to the vehicle treated control group. SWD also increased the expression of IGF-1 and BMP-2 in the proliferative and hypertrophic zones of the growth plate. Conclusions: SWD 300 mg/kg stimulates chondrocyte proliferation and new bone formation in the growth plate. Immunohistochemical studies indicate that the effects of SWD may be due to upregulation of local IGF-1 and BMP-2 expression in the growth plate, which may be considered as a GH-dependent paracrine-autocrine pathway. Graphical abstract: Image 1